PEMBELAJARAN MAHARAH AL-KITABAH PADA PROGRAM TAMBAHAN JAM PEMBELAJARAN AGAMA ISLAM DI SEKOLAH DASAR NEGERI (SDN) KOTA PALU - Fatimah, Titin; Akhiryani, Atna (Hunafa: Jurnal Studia Islamika, 2022)
This Research conducted to characterize and describe the maharah al-kitabah learning system of the additional program in Islamic religious learning hours at the public Elementary education unit at Palu Region. The object of this research are consisting of 4 (four) Elementary schools at Palu City were selected by purposive sampling tehnique. Data were collected through observation, interview and documentation. The researchs’ data were analyzed using by descriptive analysis. The results found that two forms of maharah bible learning strategies were applied in learning, namely; strategy of ta'bir muwajjah (guided); and ta'bir al-hurr strategy. Have shown that these strategies could improve the ability of students in write Arabic letters, words and sentences as well as verses of the Qur'an.